My Magic Keynote: One Game, Many Activities - Mayoral, Pedro (CIEX JOURNAL, 2017)
This workshop leads attendees through a series of activities that can be implemented in the practice of language teaching for children from 45 days (early stimulation) to secondary level adolescents. A series of songs and games are presented starting from a platform elaborated in Keynote (the equivalent of PowerPoint) that facilitates the massive participation of the audience. A tour of activities that promote the significant repetition of structures and the use of the language in constructed contexts that reproduce the reality and allow the use of the language from the communicative approach. After observing the characteristics of the didactic strategies for the teaching of English to children, the concern arises to organize a series of activities whose origin goes back to various methods of language teaching. The workshop presents a series of activities that promote meaningful learning and facilitate spaces or opportunities to implement the target language.